Aclidinium bromide inhalation powder for the long-term, maintenance treatment of bronchospasm associated with chronic obstructive pulmonary disease including chronic bronchitis and emphysema. Issue 6 (2nd June 2016) - Matera, Maria Gabriella; Sanduzzi, Alessandro; Alfano, Roberto; Cazzola, Mario
ABSTRACT: Aclidinium is a twice-daily long-acting muscarinic receptor antagonist (LAMA) with an interesting pharmacological profile. Recent evidence indicates that this LAMA, in addition to causing a significant improvement in lung function and other important supportive outcomes, such as health related quality of life, dyspnea and nighttime/early morning symptoms in patients suffering from COPD, is also able to significantly reduce the rate of exacerbations of any severity, is extremely effective in controlling the COPD symptoms, is able to reduce lung hyperinflation, and has an excellent cardiovascular safety profile. Consequently, aclidinium should be considered a first-line approach at least for the symptomatic treatment of COPD although there are still few head-to-head studies comparing this LAMA with other bronchodilators. In any case, aclidinium can be taken into account in the treatment of different COPD phenotypes (emphysema, chronic bronchitis, exacerbators and patients with overlap COPD asthma).